MATLAB Simulation of PID Control Algorithm - Ye, Likai (Journal of Theory and Practice of Engineering Science, 2024)
PID control is actually three kinds of feedback control: proportional control, integral control and differential control collectively. According to the control object and application conditions, the partial combination of these three kinds of control can be used, namely P control, PI control, PD control or the combination of the three, namely PID control in the real sense. We can call them generally PID control laws. The controller that adopts this control law is called PID controller. Parameter setting of PID controller is the core content of control system design. Parameter setting refers to the process of determining the scale coefficient, integral time and differential time of PID controller according to the characteristics of the controlled process, so as to improve the dynamic and static characteristics of the system and obtain better control effect. In the industrial application, because the control by computer is a kind of sampling control, it can only calculate the control quantity according to the deviation value of sampling time. Therefore, in the computer control system, the discretization process must be carried out first, and the differential equation of continuous system must be replaced by the difference equation of digital form.